Visible Light Promotes Decyanation Esterification Reaction of β-Ketonitriles with Dioxygen and Alcohols to α-Ketoesters - Xu, Chen; Zhang, Nan-Nan; Li, Xiao-ji; Ge, Yan-qin; Diao, Pin-hui; Guo, Cheng (Synlett, 2018)
A green and mild method has been developed for the conversion of β-ketonitriles into α-ketoesters under catalyst-free conditions. A plausible mechanism is that visible light promotes singlet oxygen generation to form the products through oxidative C–H bond functionalization and C–C σ-bond cleavage.
Keywords: visible light; α-ketoesters; β-ketonitriles; singlet oxygen; metal-free